2021
DOI: 10.1111/corg.12354
|View full text |Cite
|
Sign up to set email alerts
|

Public family firms and capital structure: A meta‐analysis

Abstract: Research Question/Issue: In this study, we examine the impact of family firm status on publicly listed firms' leverage ratios. Furthermore, we investigate the moderating role of a country's institutional setting, especially its shareholder and creditor rights, on this relationship.Research Findings/Insights: Conducting a meta-analysis on 869 effect sizes from 613 studies, we find an overall slightly negative but significant relationship between family firm status and leverage. Our results reveal a large amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 146 publications
(190 reference statements)
1
23
0
Order By: Relevance
“…Similarly, Michiels & Molly (2017) suggested that a behavioral agency approach should be adopted to better understand family firms' capital structure. According to the behavioral agency approach, under-aspiration performance is a major source of differences in behavior of firms, which should be considered when investigating family firms' capital structure (Hansen & Block, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Michiels & Molly (2017) suggested that a behavioral agency approach should be adopted to better understand family firms' capital structure. According to the behavioral agency approach, under-aspiration performance is a major source of differences in behavior of firms, which should be considered when investigating family firms' capital structure (Hansen & Block, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Over the past 20 years, capital structure and family ownership have been emerged as one of the most popular research issues in finance and management (Hansen & Block, 2021). Currently, research on these issues not only contributes to the finance literature, but also provides many meaningful managerial implications, since family is the dominant corporate type all over the world, and the capital structure is one of the most meaningful issues in corporate finance (Gottardo & Moisello, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations